(untitled) - David, Andrej; Samajova, Veronika; Zarnay, Pavel (Doprava a spoje, 2008)
Nowadays the company Sachsische Binnenhafen Oberelbe operates on the River Elbe between the Czech Republic and Germany, from the port of Lovosice to the port of Rosslau. This company which cooperates with its subsidiary Cesko-saske pristavy occupies with the creation, realization and calculation of logistics chains. They dispose of four inland ports in Germany and two ports in the Czech Republic. These ports participate on cargo transport by their transfer activities